1987
DOI: 10.1073/pnas.84.6.1694
|View full text |Cite
|
Sign up to set email alerts
|

The suprachiasmatic nuclei contain a tetrodotoxin-resistant circadian pacemaker.

Abstract: Tetrodotoxin was infused into the suprachiasmatic nuclei of unanesthetized and unrestrained rats continuously for 14 days. The internal timekeeping mechanism of the circadian pacemaker in the nuclei continued to oscillate unaffected by this treatment, although the toxin reversibly blocked function of both the input pathway for pacemaker entrainment and an output pathway for expression of the circadian drinking rhythm. Thus, Na+-dependent action potentials appear necessary for entrainment and expression of over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
150
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(162 citation statements)
references
References 34 publications
12
150
0
Order By: Relevance
“…Although previous studies show conflicting conclusions regarding the role of membrane electrical events and ion fluxes in mammalian rhythm generation (Schwartz et al, 1987;Welsh et al, 1995;Shinohara et al, 1998), our data are consistent with recent findings in mice lacking vasoactive intestinal polypeptide receptor subtype 2 (VPAC 2 ) receptors, which are activated by vasoactive intestinal polypeptide (VIP) and pituitary adenylate cyclase activating polypeptide. Mice missing the VPAC 2 receptor are unable to maintain normal behavioral rhythmicity and rhythmic expression of Per1, Per2, and Cry1 (Harmar et al, 2002).…”
Section: Discussionsupporting
confidence: 82%
“…Although previous studies show conflicting conclusions regarding the role of membrane electrical events and ion fluxes in mammalian rhythm generation (Schwartz et al, 1987;Welsh et al, 1995;Shinohara et al, 1998), our data are consistent with recent findings in mice lacking vasoactive intestinal polypeptide receptor subtype 2 (VPAC 2 ) receptors, which are activated by vasoactive intestinal polypeptide (VIP) and pituitary adenylate cyclase activating polypeptide. Mice missing the VPAC 2 receptor are unable to maintain normal behavioral rhythmicity and rhythmic expression of Per1, Per2, and Cry1 (Harmar et al, 2002).…”
Section: Discussionsupporting
confidence: 82%
“…Our strategy involved the application of TTX to disperse single-cell phases through inhibition of intercellular coupling while allowing continued cell-autonomous oscillation (28,29). TTX was then washed out, restoring coupling and allowing reorganization of the SCN over the following 8 d. We applied the maximal information coefficient (MIC) statistic (30) to bioluminescence recordings during resynchronization to identify "functional connections" within the SCN at a single-cell resolution.…”
mentioning
confidence: 99%
“…In the sinoatrial node of the heart, the coupling is electrotonic and mediated by gap junctions. In the suprachiasmatic nuclei of the mammalian circadian pacemaker, the early evidence suggested that neither gap junctions (33) nor synaptic communication (34) were essential for synchrony, leading to the proposal that the coupling was provided instead by diffusion of the inhibitory neurotransmitter ␥-aminobutyric acid (3,35) or some other diffusible substance. More recent experiments, however, seem to indicate a crucial role for actionpotential propagation and synaptic coupling in the suprachiasmatic nuclei (36).…”
Section: Discussionmentioning
confidence: 99%